Soccer and data mining - Muresan, E. M.; de Moor, B. (International Journal of Computer Science in Sport, 2002)
The purpose of our project is the full and automated analysis of soccer games. Starting from the video recording of a soccer game, the 2D coordinates of the players on the field and the 3D coordinates of the ball during the whole game are extracted by image processing and stored in a database. The interesting actions from the videos can be labelled for easy retrieval and statistics. The coordinates database and the annotation list are then processed and mined for relevant information.